INVESTIGATING IMMERSIVE ENVIRONMENT'S CONTRIBUTING FACTORS FOR LEARNERS' METACOGNITIVE STRATEGIES IN AN INDONESIAN ENGLISH VILLAGE - Pratiwi, Widya Rizky (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2023)
This paper investigated the immersive environment's contributing factors in developing learners' metacognitive learning strategies in an Indonesian English village. This study applied qualitative design through an ethnographic approach involving 14 participants from six English-speaking courses in “Kampung Inggris Pare,” Indonesia. Data were collected from observation, interviews, and photographs, then analyzed in six stages: preparing raw data, organizing data for analysis, reading all the data, coding data, communicating the theme/description, and interpreting the meaning. The results indicated that the English village accommodates establishing the Authentic Immersion Environment, English Camps, and exciting classroom activities. The elements assisted the learners in centering, planning, arranging, monitoring, and evaluating their learning while studying and staying for some months in this environment. This study promotes three elements of an English village-based immersion environment and presents how their role commits to developing learners' metacognitive learning strategies in learning English. Abstrak: Makalah ini menyelidiki faktor-faktor pendukung lingkungan imersif dalam mengembangkan strategi pembelajaran metakognitif siswa di kampung bahasa Inggris Indonesia. Penelitian ini menerapkan desain kualitatif melalui pendekatan etnografi yang melibatkan 14 responden dari enam kursus berbahasa Inggris di “Kampung Inggris Pare,” Indonesia. Data dikumpulkan dari observasi, wawancara, dan foto, kemudian dianalisis dalam enam tahap: menyiapkan data mentah, mengorganisir data untuk analisis, membaca semua data, mengkodekan data, mengkomunikasikan tema/deskripsi, dan menafsirkan makna. Hasil penelitian menunjukkan bahwa kampung Inggris mengakomodasi pembentukan Authentic Immersion Environment, English Camps, dan kegiatan kelas yang menyenangkan. Unsur-unsur tersebut membantu siswa dalam memusatkan, merencanakan, mengatur, memantau, dan mengevaluasi pembelajaran mereka selama belajar dan tinggal beberapa bulan di lingkungan tersebut. Penelitian ini mempromosikan tiga element lingkungan imersi berbasis kampung bahasa Inggris dan menyajikan bagaimana peran mereka berkomitmen untuk mengembangkan strategi pembelajaran metakognitif siswa dalam belajar bahasa Inggris.